The activity of the Polish Legation in Oslo, 1946–1947 - Denkiewicz-Szczepaniak, Emilia (Studia Scandinavica, 2020)
The activity of the Polish Legation in Oslo in the years 1946–1947 is one of the most important and, at the same time, one of the most difficult periods in the history of Polish-Norwegian relations. The introduction explains the reasons for such a late sending of a Polish representative, Mieczysław Rogalski, to Norway. Section I presents the biography of Rogalski as well as the experience he gained while working for the Ministry of Foreign Affairs. The next section describes the negative attitude that the Polish diplomat had during his contacts with the Norwegian Ministry of Foreign Affairs (Utenriksdepartementet), especially in relation to further repatriation of Poles, which was started in autumn 1945 by the liaison officers of the Polish government in exile. Section III presents the diplomatic successes Rogalski had in his relations with Norwegian politicians and also indicates how good his orientation in Norway’s foreign policy was. Finally, the last section contains a description of Legation problems regarding mutual exchange of decorations and orders between Poland and Norway, including in particular political activities connected with the organization of celebrations commemorating the victory at Narvik. The activity of the Polish Legation in Oslo in the years 1946–1947 is one of the most important and, at the same time, one of the most difficult periods in the history of Polish-Norwegian relations. The introduction explains the reasons for such a late sending of a Polish representative, Mieczysław Rogalski, to Norway. Section I presents the biography of Rogalski as well as the experience he gained while working for the Ministry of Foreign Affairs. The next section describes the negative attitude that the Polish diplomat had during his contacts with the Norwegian Ministry of Foreign Affairs (Utenriksdepartementet), especially in relation to further repatriation of Poles, which was started in autumn 1945 by the liaison officers of the Polish government in exile. Section III presents the diplomatic ...